Kajian Literatur Integrasi Aritmetika Sosial dengan Nilai-Nilai Fiqih dalam Zakat pada Pembelajaran Matematika - Putri, Rizqillah Ayunita; Faradiba, Surya Sari (Mandalika Mathematics and Educations Journal, 2025)
This study aims to examine the integration of social arithmetic with Islamic jurisprudence (fiqh) values, particularly zakat, in mathematics learning. The method used is a systematic literature review (SLR) with five stages: formulating research questions, identifying relevant articles, assessing study quality, summarizing evidence, and interpreting findings. Articles were searched using the keywords "social arithmetic" and "zakat" on Google Scholar, with articles published between 2020 and 2025. Of the 15 selected articles, five met the qualifications and were analyzed in depth. The results showed two main findings: first, students' understanding of the concepts of percentages and fractions significantly improved through the integration of zakat in mathematics learning; second, Islamic character values such as honesty, responsibility, and social concern were strengthened. These findings confirm that mathematics learning integrated with Islamic jurisprudence (zakat) values not only strengthens students' cognitive competence but also shapes religious personalities in accordance with the goals of Islamic education. Therefore, this integration needs to be continuously developed in school learning.